The Influence of Religiosity, Taxpayer Environment and Gender Against Individual Taxpayer Compliance - Adisty, Putri; Syahdan, Saifhul Anuar; Ruwanti, Gemi; Boedi, Soelistijono (Asosiasi Dosen Akuntansi Indonesia, 2025)
This study aims to obtain empirical evidence of the influence of religiosity, environment and gender on taxpayer compliance, as well as test whether there are differences in gender on taxpayer compliance. The population of this study is MAN Teachers in Banjarmasin City. The sampling technique uses saturated sampling. The number of samples obtained was 66 respondents. The data analysis technique used is multiple linear regression. The results showed that religiosity had a positive effect on taxpayer compliance, while environment and gender did not affect taxpayer compliance. The results of this study also prove that there is no difference between the compliance of male and female taxpayers